2020
DOI: 10.1016/j.jebo.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk preferences of children and adolescents in relation to gender, cognitive skills, soft skills, and executive functions

Abstract: We conduct experiments eliciting risk preferences with over 1,400 children and adolescents aged 3-15 years old. We complement our data with an assessment of cognitive and executive function skills. First, we find that adolescent girls display significantly greater risk aversion than adolescent boys. This pattern is not observed among young children, suggesting that the gender gap in risk preferences emerges in early adolescence. Second, we find that at all ages in our study, cognitive skills (specifically math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…It is plausible that this repeated playing and honing of their skills could have contributed to a better appreciation for the concept of risk-taking, leading to a reduction in risk aversion. Our findings are consistent with evidence showing that risk preferences share an association with aspects of cognitive ability (Frederick 2005;Dohmen et al 2010;Benjamin et al 2013 andAndreoni et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is plausible that this repeated playing and honing of their skills could have contributed to a better appreciation for the concept of risk-taking, leading to a reduction in risk aversion. Our findings are consistent with evidence showing that risk preferences share an association with aspects of cognitive ability (Frederick 2005;Dohmen et al 2010;Benjamin et al 2013 andAndreoni et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, although a large literature in experimental economics has focused on the role of risk preferences in explaining life outcomes (e.g. Dohmen et al 2011;Sutter et al 2013), surprisingly little is known about differences in risk preferences at an early age and how these preferences are developed, or how they may alter the life paths of students (Andreoni et al, 2019). Chess may be of particular interest to policymakers who are interested in identifying programs that can provide early stimulation and help develop such important "soft" life skills in children during their formative years.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have shown, with plausible strategies for identifying causal impacts, that girls' attitudes toward, and willingness to study, quantitative and scientific subjects are affected by the social influence of family, peers, and role models on their perceived competence in math and beliefs about gender‐appropriate behavior. This may explain why many gender gaps in performance and attitudes, such as the male advantage in math and higher levels of female risk aversion, emerge only in adolescence as gender identity concerns intensify (Fahle and Reardon, 2018; Andreoni et al ., forthcoming). There has been less research in economics on the educational underperformance of boys, and much of it is descriptive, pointing to behavioral problems more prevalent among boys as evidence of a deficit in non‐cognitive skills that increases the costs of persisting in formal education (Goldin et al ., 2006; Becker et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature we survey, there is some evidence that skills move in tandem. For example, studies find a correlation between risk preferences and cognitive abilities (Benjamin et al, 2013;Andreoni et al, 2019a). Such correlations also have implications for the identification of skills and preferences, which we discuss in sub-section 10.4.…”
Section: Development Of Economic Preferencesmentioning
confidence: 89%